Role of EMG in Congenital Hypotonia with Favorable Outcome - Pisani, F.; Carboni, P. (Acta Biomedica Atenei Parmensis, 2005)
Background: Since hypotonia is the phenotype of several clinical conditions that do not always lead to a favorable outcome, prompt diagnosis is important. Congenital Hypotonia with Favorable Outcome (CHFO), an underestimated condition, should be rapidly differentiated from other more serious hypotonic states by means of simple, effective and only slightly invasive instrumental diagnostic examinations. Aim:We analyzed the electromyographic data of a group of patients with CHFO and compared them with data taken from their muscle biopsies to evidence the utility of the electromyographic study (EMG) in this condition. Methods: We performed EMG, nerve conduction study (NCS) and muscle biopsy on 41 subjects with a diagnosis of CHFO (age range 9 months to 12 years, mean age, 6.7 years). Results: No specific EMG findings were observed.Muscle biopsy was normal in all subjects, and we obtained concordance between biopsy and EMG in 85% of the subjects (35/41). Conclusion: A normal EMG examination helps investigators to exclude several neurological diseases characterized by hypotonia and it can provide valuable complementary information to confirm the clinical diagnosis of CHFO.